2015
DOI: 10.2174/1745017901511010150
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation by Light and Sound: Therapeutics Effects in Humans. Systematic Review

Abstract: Introduction : The objective of the study was to make a systematic review of published studies that used the brain stimulation by light and sound as means to optimize brain function and increase the different treatments. Methods : The methods followed the Prisma model for eligibility of studies. Results : Four studies on the systematic review were included 3 experimental studies and 1 case report. Two of these studies were focused in learning and sportive performance, and 2 focused on increasing physical and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
18
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 3 publications
1
18
0
2
Order By: Relevance
“…Nonetheless, this study demonstrates that external stimulation applied to sensory pathways can alter brain activity, through the medium of neuroplasticity in this case, with resultant therapeutic effect possible. Da Silva et al conducted a review in 2015 into the use of light and sound stimulation as a therapeutic modality [ 91 ]. It is perhaps suggestive of how new this field is that only four studies were found and reported on; indeed, it was noted in [ 91 ] that light and sound stimulation are the least tested modalities of brain stimulation.…”
Section: Review Of Gamma Band Stimulatory and Related Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonetheless, this study demonstrates that external stimulation applied to sensory pathways can alter brain activity, through the medium of neuroplasticity in this case, with resultant therapeutic effect possible. Da Silva et al conducted a review in 2015 into the use of light and sound stimulation as a therapeutic modality [ 91 ]. It is perhaps suggestive of how new this field is that only four studies were found and reported on; indeed, it was noted in [ 91 ] that light and sound stimulation are the least tested modalities of brain stimulation.…”
Section: Review Of Gamma Band Stimulatory and Related Studiesmentioning
confidence: 99%
“…Da Silva et al conducted a review in 2015 into the use of light and sound stimulation as a therapeutic modality [ 91 ]. It is perhaps suggestive of how new this field is that only four studies were found and reported on; indeed, it was noted in [ 91 ] that light and sound stimulation are the least tested modalities of brain stimulation. Two of the studies were concerned with sports performance, with the other two health care related with one being a case report.…”
Section: Review Of Gamma Band Stimulatory and Related Studiesmentioning
confidence: 99%
“…The frequencies imposed on the brain are perceived by the olive nucleus and its reception is made by the thalamus, which is the structure responsible for receiving and filtering external stimuli together with the reticular activating system. This rhythm is sent to the cortex which, in a few minutes, accompanies the imposed frequency (2,3,5,7,12,13).…”
Section: Mechanism Of Binaural Wavesmentioning
confidence: 99%
“…T he brain works with electrochemical shots, generating the brain waves that represent the activity of the cortex. The basic frequencies of brain functioning: gamma (30-70 Hz), beta (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30), alpha (8)(9)(10)(11)(12)(13), theta (4-8 Hz) and delta (1)(2)(3)(4). Cortical activity is related to states of consciousness, the amplitude of these waves being directly proportional to the number of neurons in the cortex (1,2).…”
mentioning
confidence: 99%
See 1 more Smart Citation